2013
DOI: 10.7567/apex.6.081303
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Si2N2O Microcrystalline Precipitates near the Quartz Crucible Wall Coated with Silicon Nitride in Cast-Grown Silicon

Abstract: The chemical reaction near the crucible wall during directional solidification of Si crystals for solar cells has been investigated. Fragments of the crucible that were used for the crystal growth of a Si ingot were examined. As results, we found that a chemical reaction took place at the coating/crucible interface and that silicon oxynitride particles precipitated near the crucible wall. The oxynitride precipitates were determined as stoichiometric Si2N2O and were revealed not to be amorphous but of orthorhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Control of these light-element impurities, i.e., interstitial oxygen (O i ) and substitutional carbon (C s ), has become essential because light-element impurities affect solar sell performance through defect formation. [17][18][19][20][21][22][23][24][25][26][27] It is necessary to accurately clarify the mechanism of generation of the light-element impurities in Si crystals grown by the seed-casting method to develop methods to suppress the degradation in solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Control of these light-element impurities, i.e., interstitial oxygen (O i ) and substitutional carbon (C s ), has become essential because light-element impurities affect solar sell performance through defect formation. [17][18][19][20][21][22][23][24][25][26][27] It is necessary to accurately clarify the mechanism of generation of the light-element impurities in Si crystals grown by the seed-casting method to develop methods to suppress the degradation in solar cell efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of the thermodynamics of amorphous phases in the Si–O–N system is also important when considering the solubility, nucleation, and growth of various precipitates in high‐temperature processes involving the growth and refinement of crystalline phases such as Si, SiO 2 , Si 3 N 4 , and Si 2 N 2 O . Examination of the thermochemistry of a‐SiNH and a‐SiNOH materials will also broaden the understanding of the energy landscape in the Si–O–N and Si–O–N–H systems by examining previously unexplored portions of these phase diagrams.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, it has been revealed that oxygen precipitates are often formed in the crystal during crystal growth and reduce the carrier lifetime. [6][7][8][9][10] Furthermore, GBs and dislocations also act as carrier recombination centers of minority carriers and affect the cell performance. 11,12) There have been many studies investigating oxygen and oxygen precipitates in sc-Si being used for large-scale integration (LSI) devices.…”
Section: Introductionmentioning
confidence: 99%